How do virtual streamers affect purchase intention in the live streaming context? A presence perspective. (July 2023) - Gao, Wei; Jiang, Ning; Guo, Qingqing
Abstract: The rise of live streaming commerce has attracted attention from scholars and practitioners as a new opportunity to reach consumers. However, few studies have focused on the role of virtual streamers in this context. Based on the stimulus organism response framework, we explore the impact of three characteristics of virtual streamers—likeability, animacy, and responsiveness—on social presence, telepresence, and purchase intention. We use partial least squares structural equation modeling analysis with online survey data from 378 consumers concerning their experiences of viewing virtual streamers. The findings indicate that likeability, animacy, and responsiveness enhance social presence and telepresence, which then promote purchase intention. Likeability and responsiveness directly increase purchase intention, but animacy does not. Multi-group analysis reveals differences between the effects of humanoid and zoonotic virtual streamers on social presence and telepresence. These results shed light on the role of virtual streamer characteristics and contribute to the literature on live streaming commerce, presence, and virtual humans.